Sovereign risk and Dutch disease - Carlos Esquivel (Rutgers University, Department of Economics, 2024)
I study how, in the presence of default risk, the Dutch disease amplifies an inefficiency in the sectoral allocation of capital. I develop a sovereign default model with production of tradable and non-tradable goods, and endowments of commodities. Default incentives increase when more capital is allocated to non-traded production. Households do not internalize this effect, giving rise to over-investment in the non-traded sector. Commodity windfalls amplify this inefficiency through the classic Dutch disease mechanism and an increased desire to borrow. Policies that reduce the returns of non-traded capital, such as exchange rate sterilization, ameliorate the degree of over-investment during commodity windfalls. Evidence from spreads, commodity endowments, and exchange rate data supports the main findings of the model.
Keywords: F34; F41; H63; 330; Sovereign default; Dutch disease; real exchange rates